The trade-off between the transmission of chemical cues and parasites: behavioral interactions between leaf-cutting ant workers of different age classes - Lopes, Juliane F. S. [UNESP]; Camargo, Roberto da Silva [UNESP]; Forti, Luiz C. [UNESP]; Hughes, William O. H. (Soc Brasileira Entomologia, 2017)
Social animals are faced with an intriguing dilemma. On the one hand, interactions between individuals are essential to exchange information and to promote cohesion, while on the other hand such interactions carry with them the risk of catching and transmitting parasites. This trade-off is particularly significant for social insects because low within-colony genetic diversity makes their colonies potentially vulnerable to parasites while frequent interactions are essential to the development of the colonial odor profile necessary for nestmate recognition. Here we investigate whether social interactions between young and old leaf-cutting ant workers show evidence of this trade-off. We find that old workers engage in more selfgrooming and mandibular scraping than young workers, both in keeping with old workers having been more exposed to parasites. In contrast, we find that young workers engaged in more allogrooming than old workers, which seems likely to have a different motivation possibly the transfer of recognition cues. Furthermore, young workers tended to engage in allogrooming with other young workers, although it was the old workers that were most active and with whom allogrooming would seem likely to optimize information or chemicals transfer. This suggests that young workers may be attempting to minimize the risk of parasite transmission during their social interactions. Although limited to behavioral data, these results hint that ant workers may be sensitive to the trade-off between the transmission of recognition cues and disease, and adjust their social interactions accordingly. (C) 2016 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda.
Keywords: Acromyrmex; Age polyethism; Behavioral interaction; Chemicals transfer